2006
DOI: 10.1002/pssa.200563132
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and surface spin excitations in thin films of manganites

Abstract: A review of experimental studies of magnon excitations in manganites is presented. A microwave resonance technique, in particular a spin‐wave resonance (SWR) technique, is shown to allow the study of not only bulk properties but also surface properties of manganite films. There are two main theoretical approaches used to interpret the SWR spectra: the volume inhomogeneity and the surface inhomogeneity models. The latter, introduced by Puszkarski, allows the interpretation of the observed surface magnon excitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
8
2
Order By: Relevance
“…Contrary to Ref. [17] we found that oxygen annealing at different temperatures from 600 0 C to 900 0 C does not ameliorate the SWR spectrum in our films but introduces additional splitting. In particular, the resonant peaks in annealed films split into many narrow lines with the spacing of ∼15 Oe.…”
Section: Methodscontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to Ref. [17] we found that oxygen annealing at different temperatures from 600 0 C to 900 0 C does not ameliorate the SWR spectrum in our films but introduces additional splitting. In particular, the resonant peaks in annealed films split into many narrow lines with the spacing of ∼15 Oe.…”
Section: Methodscontrasting
confidence: 99%
“…The difference between our results and those of Ref. [17] is probably related to the fact that we operate with the film of different composition and on different substrate. …”
Section: Methodscontrasting
confidence: 99%
See 3 more Smart Citations